Thyroid hormones and menstrual cycle function in a longitudinal cohort of premenopausal women. Issue 3 (8th March 2018) - Jacobson, Melanie H.; Howards, Penelope P.; Darrow, Lyndsey A.; Meadows, Juliana W.; Kesner, James S.; Spencer, Jessica B.; Terrell, Metrecia L.; Marcus, Michele
Abstract: Background: Previous studies have reported that hyperthyroid and hypothyroid women experience menstrual irregularities more often compared with euthyroid women, but reasons for this are not well‐understood and studies on thyroid hormones among euthyroid women are lacking. In a prospective cohort study of euthyroid women, this study characterised the relationship between thyroid hormone concentrations and prospectively collected menstrual function outcomes. Methods: Between 2004‐2014, 86 euthyroid premenopausal women not lactating or taking hormonal medications participated in a study measuring menstrual function. Serum thyroid hormones were measured before the menstrual function study began. Women then collected first morning urine voids and completed daily bleeding diaries every day for three cycles. Urinary oestrogen and progesterone metabolites (estrone 3‐glucuronide (E1 3G) and pregnanediol 3‐glucuronide (Pd3G)) and follicle‐stimulating hormone were measured and adjusted for creatinine (Cr). Results: Total thyroxine (T4 ) concentrations were positively associated with Pd3G and E1 3G. Women with higher (vs lower) T4 had greater luteal phase maximum Pd3G (Pd3G = 11.7 μg/mg Cr for women with high T4 vs Pd3G = 9.5 and 8.1 μg/mg Cr for women with medium and low T4, respectively) and greater follicular phase maximum E1 3G (E1 3G = 41.7 ng/mg Cr for women with high T4 vs E1 3G = 34.3 and 33.7 ng/mg Cr for women with medium and low T4, respectively). Conclusions: Circulating thyroid hormone concentrations were associated with subtle differences in menstrual cycle function outcomes, particularly sex steroid hormone levels in healthy women. Results contribute to the understanding of the relationship between thyroid function and the menstrual cycle, and may have implications for fertility and chronic disease.